Book review: Malinowski, J. (2021). The psychology of dreaming - Schredl, Michael (International journal of dream research, 2021)
The book of Josie Malinowksi is a well-written and informative introduction into psychological dream research. After definitions and a brief review of the history of dreaming, the author integrates many of the current theories about dream function, e.g., processing of emotions, Social Simulation theory, or dreaming as playing. In addition, clinical aspects, e.g., dream sharing, are reviewed with the interesting idea that working with dreams in waking might enhance the function of dreams. Phenomena like lucid dreams, precognitive dreaming, posttraumatic dreams, and sleep paralysis which are currently discussed widely are presented in a very concise format, clearly demonstrating the author’s knowledge that she has accumulated over more than 10 years of dream research. Lastly, the author emphasizes that dream researchers - like scientists in general - should also discuss the ethical implications of their findings, e.g., when influencing dream content with application of external stimuli.